Sodium New Houttuyfonate Inhibits Candida albicans Biofilm Formation by Inhibiting the Ras1-cAMP-Efg1 Pathway Revealed by RNA-seq - Wu, Jiadi; Wu, Daqiang; Zhao, Yeye; Si, Yuanqing; Mei, Longfei; Shao, Jing; Wang, Tianming; Yan, Guiming; Wang, Changzhong (Frontiers in Microbiology, 2020)
Here, we aim to investigate the antifungal effect and mechanism of action of sodium new houttuyfonate (SNH) against Candida albicans. Microdilution analysis results showed that SNH possesses potent inhibitory activity against C. albicans SC5314, with a MIC80 of 256 μg/mL. Furthermore, we found that SNH can effectively inhibit the initial adhesion of C. albicans. Inverted microscopy, crystal violet staining, scanning electron microscopy and confocal laser scanning microscopy results showed that morphological changes during the transition from yeast to hypha and the biofilm formation of C. albicans are repressed by SNH treatment. We also found that SNH can effectively inhibit the biofilm formation of clinical C. albicans strains (Z103, Z3044, Z1402, Z1407) and SNH in combination with fluconazole, berberine chloride, caspofungin and itraconazole antifungal agents can synergistically inhibit the biofilm formation of C. albicans. Eukaryotic transcriptome sequencing and qRT-PCR results showed that SNH treatment resulted in significantly down-regulated expression in several biofilm formation related genes in the Ras1-cAMP-Efg1 pathway (ALS1, ALA1, ALS3, EAP1, RAS1, EFG1, HWP1 and TEC1) and significantly up-regulated expression in yeast form-associated genes (YWP1 and RHD1). We also found that SNH can effectively reduce the production of key messenger cAMP in the Ras1-cAMP-Efg1 pathway. Furthermore, using Galleria mellonella as an in vivo model we found that SNH can effectively treat C. albicans infection in vivo. Our presented results suggest that SNH exhibits potential antibiofilm effects related to inhibiting the Ras1-cAMP-Efg1 pathway in the biofilm formation of C. albicans.